PENINGKATAN PERTUMBUHAN DAN PRODUKSI JAGUNG UNGU VARIETAS JANTAN F1 MELALUI APLIKASI NUTRISI ZINC - Adhinugraha, Qudus Sabha; Agustiansyah, Agustiansyah; Timotiwu, Paul Benyamin; Rahayu, Dwi (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Maize was one of the most important food crops in the world; therefore, the demand for corn continued to increase in line with the growing global population. In general, increasing maize productivity was achieved by fulfilling the requirements for macro and micronutrients, as well as ensuring supportive environmental conditions so that the plants could grow well. One of the essential micronutrients needed by plants was zinc. This study aimed to determine the effect of zinc nutrient application on the growth and yield of purple maize of the Jantan F1 variety, as well as to identify the optimal zinc application treatment to enhance the growth and production of this variety. This research was conducted from September 14, 2024 to November 23, 2024 at the Integrated Field Laboratory and Seed and Plant Breeding Laboratory, Faculty of Agriculture, University of Lampung. The research was conducted using a Randomized Complete Block Design (RCBD) consisting of five treatments with a single factor: P0 (control/no zinc application); P1 (seed priming with Zn 0.5%); P2 (seed priming with Zn 0.5% + foliar Zn 0.1% at 10, 20, and 30 DAP); P3 (seed priming with Zn 0.5% + foliar Zn 0.1% at 30, 40, and 50 DAP); and P4 (seed priming with Zn 0.5% + foliar Zn 0.1% at anthesis, 7 days after pollination (DAPn), and 14 DAPn). The experiment was conducted with four replications, resulting in 20 experimental units. The results showed that the application of zinc nutrients to the purple maize of the Jantan F1 variety improved plant growth, as reflected in plant height, number of leaves, leaf area, and chlorophyll content. In addition, zinc nutrient application also increased yield, as indicated by variables such as cob weight with husk, cob weight without husk, number of rows per cob, and number of kernels per cob. The best treatment was zinc priming 0.5% combined with foliar Zn 0.1% applied at the anthesis stage, 7 DAPn, and 14 DAPn.